Dynamic ECG signal quality evaluation based on persistent homology and GoogLeNet method - Ren, Yonglian; Liu, Feifei; Xia, Shengxiang; Shi, Shuhua; Chen, Lei; Wang, Ziyu (Frontiers in Neuroscience, 2023)
Cardiovascular disease is a serious health problem. Continuous Electrocardiograph (ECG) monitoring plays a vital role in the early detection of cardiovascular disease. As the Internet of Things technology continues to mature, wearable ECG signal monitors have been widely used. However, dynamic ECG signals are extremely susceptible to contamination. Therefore, it is necessary to evaluate the quality of wearable dynamic ECG signals. The topological data analysis method (TDA) with persistent homology, which can effectively capture the topological information of high-dimensional data space, has been widely studied. In this study, a brand-new quality assessment method of wearable dynamic ECG signals was proposed based on the TDA with persistent homology method. The point cloud of an ECG signal was constructed, and then the complex sequence was generated and displayed as a persistent barcode. Finally, GoogLeNet based on the transfer learning model with a tenfold cross-validation method was used to train the classification model. 12-leads ECGs Dataset and single-lead ECGs Dataset, established based on the 2011 PhysioNet/CinC challenge dataset, were both used to verify the performance of this method. In the study, 773 ‘acceptable’ and 225 ‘unacceptable’ signals were used as 12-leads ECGs Dataset. We relabeled 12000 ECG signals in the challenge dataset, and treated them as single-lead ECGs Dataset after empty lead detection and balance datasets. Compared with the traditional ECG signal quality assessment method mainly based on waveform characteristics and time-frequency characteristics, the performance of the quality assessment method proposed. In this study, the classification performance of the proposed method are fairly great, mAcc=98.04%, F1=98.40%, Se=97.15%, Sp=98.93% for 12-leads ECGs Dataset and mAcc=98.55%, F1=98.62%, Se=98.37%, Sp=98.85% for single-lead ECGs Dataset.